2019
DOI: 10.4103/bc.bc_25_18
|View full text |Cite
|
Sign up to set email alerts
|

Increase in cerebral blood flow indicated by increased cerebral arterial area and pixel intensity on brain magnetic resonance angiogram following correction of cervical lordosis

Abstract: CONTEXT: Loss of cervical lordosis is associated with decreased vertebral artery hemodynamics. AIM: The aim of this study is to evaluate cerebral blood flow changes on brain magnetic resonance angiogram (MRA) in patients with loss of cervical lordosis before and following correction of cervical lordosis. SETTINGS AND DESIGN: This study is a retrospective consecutive case series of patients in a private practice. MATERIALS AND M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 26 publications
0
5
0
Order By: Relevance
“…Furthermore, since abnormal sagittal plane postures cause an increase in stress and strain on both neural and vascular tissues in the cervical spine [46,47], and it is known that neuronal tissues are highly oxygen-energy dependent [53], it is probable that increased neural strain coupled with reductions in respiratory efficiency may be a mechanism subtly impacting oxygenation to the spinal cord, nerve roots, and cerebral areas, leading to the alteration in the sensorimotor integration disturbances identified in our study. Supporting these assertions, there is evidence of an alteration in vertebral artery hemodynamics and cerebral blood flow intensity on MRA due to alterations in sagittal cervical alignment [54,55].…”
Section: Central Somatosensory Conduction Timementioning
confidence: 85%
“…Furthermore, since abnormal sagittal plane postures cause an increase in stress and strain on both neural and vascular tissues in the cervical spine [46,47], and it is known that neuronal tissues are highly oxygen-energy dependent [53], it is probable that increased neural strain coupled with reductions in respiratory efficiency may be a mechanism subtly impacting oxygenation to the spinal cord, nerve roots, and cerebral areas, leading to the alteration in the sensorimotor integration disturbances identified in our study. Supporting these assertions, there is evidence of an alteration in vertebral artery hemodynamics and cerebral blood flow intensity on MRA due to alterations in sagittal cervical alignment [54,55].…”
Section: Central Somatosensory Conduction Timementioning
confidence: 85%
“…Consequently, these patients may experience impaired postural perception and balance, potentially leading to negative impacts on their gait (Kim & Oh, 2014; Schinkel-Ivy et al, 2016; Tyson et al, 2006). Additionally, FHP may decrease blood flow to the brain and negatively affect neuroplastic processes, potentially impairing the development of balance and gait (Katz et al, 2019). Muscle and joint dysfunction associated with FHP may improve with mobilization (suboccipital myofacial release and joint mobilization).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, these techniques may increase the activity of motor neurons that activate proprioceptive receptors, positively affecting balance (Gyer et al, 2019; Hengeveld & Banks, 2013). Cervical mobilization (CM) may improve balance and gait posture (GP) by reducing muscle spasms, correcting dysfunctions in cervical joints, and accelerating blood flow to the brain (Gyer et al, 2019; Katz et al, 2019) Although some investigators have reported positive effects of CM on balance in healthy individuals and in patients with orthopedic problems, there has been limited research examining CM effects on balance and GP in stroke survivors (T. Choi et al, 2019; T.S. Choi et al, 2020; Maden et al, 2022), leading us to undertake this investigation.…”
Section: Introductionmentioning
confidence: 99%
“…There is evidence to suggest that abnormal sagittal cervical alignment may place a constant, increased strain on neural and vascular elements in the cervical spine, directly impairing the blood flow to the spinal cord, nerve roots and cerebral areas 58 60 . For example, Katz et al 61 identified a linear correlation between cervical lordotic curve magnitude induced on the cervical denneroll orthtoic and increased MRI-angiogram cerebral blood flow pixel intensity.…”
Section: Discussionmentioning
confidence: 99%